EXPLORING FRIEZE PATTERNS IN LOTIS AMANUBAN WOVEN FABRICS: INTEGRATION OF TEKE AND BIKLUSU MOTIFS INTO MATHEMATICS EDUCATION - Daniel, Farida; Turmudi, Turmudi; Juandi, Dadang; Kusnandi, Kusnandi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
AbstractThe teke (gecko) and biklusu (lizard) motifs in lotis woven fabrics represent symbolic and spiritual values in Amanuban culture while also containing mathematical structures. However, these mathematical aspects are rarely explored, and local weaving traditions are seldom integrated into formal mathematics learning. This gap has led to limited use of cultural resources in supporting students’ understanding of geometry. Therefore, this study identifies the types of frieze patterns in three variants of these motifs and explores their potential for integration into mathematics education. A descriptive qualitative approach was employed, utilizing direct observation, documentation, and interviews with weavers and cultural elders. The primary data consisted of visual representations of the three motifs, which were analyzed through isometric transformations including translation, vertical and horizontal reflection, 180° rotation, and glide reflection. The classification was based on the seven types of frieze patterns as defined by the one-dimensional isometry group theory. The findings reveal that two motifs correspond to the F6 frieze pattern type, while one aligns with the F7 type, demonstrating varying degrees of geometric symmetry complexity. The teke and biklusu motifs can serve as effective contextual tools for mathematics instruction across educational levels, from pattern recognition in primary school to advanced discussions of isometry group theory in higher education. This approach aligns with the goals of the Merdeka Curriculum by linking mathematics learning to meaningful local contexts.